Positive Impact of Targeted Educational Intervention in Children With Low Adherence to Growth Hormone Treatment Identified by Use of the Easypod™ Electronic Auto-injector Device - Assefi, Aria Reza; Roca, Fernanda; Rubstein, Adrián; Chareca, Cinthia (Frontiers in Medical Technology, 2021)
Background: It is important to identify patients with low adherence to recombinant human growth hormone (r-hGH) therapy and initiate actions to improve adherence. The Merck Patient Support Program (PSP) aims to raise the awareness of these patients and their parents of the importance of good adherence in achieving optimal growth outcomes. The easypod™ digitally-enhanced injection device provides accurate, reliable adherence data for the PSP by recording the exact dose, time and date of injections given. In this study, we aimed to measure the effect of an educational intervention on adherence in patients using the easypod™ device to deliver their r-GH therapy. Methods: This was a 12-month observational, retrospective cohort study. Patients previously identified by data recorded from their easypod™ injection device as having low adherence (<80%) were followed over the 6 months before and after a targeted educational visit by a PSP nurse. Patient adherence and demographic data were extracted from the PSP database. Statistical analyzes were carried out with STATA 15.0 software. Results: Data from 80 patients (65% male) with low adherence were analyzed. Patients were aged 2–18 (mean: 11.77) years with diagnoses of growth hormone deficiency (71.25%), small for gestational age (20%), Turner syndrome (7.50%) and chronic renal disease (1.25%). Duration of treatment was 0.40–11.13 (median: 3.62) years. At baseline, median adherence to r-hGH therapy was 67%; after the intervention it increased to 76%, a statistically significant median improvement of 9% (p=0.0000, Wilcoxon signed-rank test). Additionally, 36% (29/80) of patients increased their adherence to r-hGH therapy to ‘good’ (≥80%). Both changes were clinically relevant. Conclusions: We conclude that a nurse-led educational intervention, supported by digital medication adherence monitoring, is a simple method to improve adherence to r hGH therapy, and recommend this intervention to reduce the gap between the indication/recommendation of the specialist and patients’ behavior.